2008
DOI: 10.1164/rccm.200706-821oc
|View full text |Cite
|
Sign up to set email alerts
|

Pesticides and Atopic and Nonatopic Asthma among Farm Women in the Agricultural Health Study

Abstract: Rationale: Risk factors for asthma among farm women are understudied. Objectives: We evaluated pesticide and other occupational exposures as risk factors for adult-onset asthma. Methods: Studying 25,814 farm women in the Agricultural Health Study, we used self-reported history of doctor-diagnosed asthma with or without eczema and/or hay fever to create two case groups: patients with atopic asthma and those with nonatopic asthma. We assessed disease-exposure associations with polytomous logistic regression. Mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
4
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 39 publications
(44 reference statements)
5
118
4
4
Order By: Relevance
“…The AHS cohort has given rise to a series of studies on exposure to specific pesticides and showed that numerous pesticides were significantly associated with allergic asthma [52], wheeze [49,51] and chronic bronchitis [58]. It was also shown that accidental exposure or pesticide poisoning were associated with an increased risk of allergic and nonallergic asthma [59].…”
Section: Discussionmentioning
confidence: 99%
“…The AHS cohort has given rise to a series of studies on exposure to specific pesticides and showed that numerous pesticides were significantly associated with allergic asthma [52], wheeze [49,51] and chronic bronchitis [58]. It was also shown that accidental exposure or pesticide poisoning were associated with an increased risk of allergic and nonallergic asthma [59].…”
Section: Discussionmentioning
confidence: 99%
“…A large subpopulation of the United States is sensitized to allergens (atopic) (21). Although agricultural workers are more often nonatopic than individuals working in other sectors or living in urban areas (22), occupational exposure to OPs is associated with increased allergic asthma in agricultural workers (23,24). In nonsensitized guinea pigs, parathioninduced airway hyperreactivity and M2 muscarinic receptor dysfunction is not mediated by eosinophils (14), but instead by TNF-a (15).…”
Section: Clinical Relevancementioning
confidence: 99%
“…It appears that microbefacilitated immune maturation can be nullified by problematic exposure during critical windows of development to other environmental factors. For example, Hoppin et al [76] reported from the U.S. National Agricultural Health Study that direct exposure to pesticides appeared to nullify the beneficial aspects for women of growing up on a farm relative to risk of atopic asthma. Mai et al [77] also found that a largely fast food diet could undermine the beneficial aspects of breastfeeding relative to risk of asthma.…”
Section: Other Routes and Considerations For Developmentallyprogrammementioning
confidence: 99%